Eliza Lee Cabot Follen correspondence - Follen, Eliza Lee Cabot 1787-1860.
Letter (1859) of Eliza Follan to Mrs. (?) Stearns regarding the approaching execution of John Brown.
Author and abolitionist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brown, John, -- 1800-1859.; Abolitionists; Authors